ANALISIS TROUBLESHOOTING ENGINE SEPEDA MOTOR YAMAHA VIXION - Anugrah, Rinasa Agistya (Politeknik Harapan Bersama Tegal, 2021)
Motorcycle engine performance must always be maintained in the best condition. To maintain engine performance can be done with regular maintenance. The troubleshooting step is a reference in performing engine maintenance and repair. This study aims to perform troubleshooting analysis on the Yamaha Vixion engine. The method in this study is the removal, inspection, and reassembly of existing components based on the Yamaha Vixion manual or service manual. The results of the inspection and measurement are compared with the standards in the Yamaha Vixion manual or service manual. This method is used to determine the troubleshooting analysis on the Yamaha Vixion engine. In the component inspection step, the component measurement results are compared with the standard. The result of measuring components that exceed their standard limits or intervals means that the component has been damaged, worn, and or is not suitable for use. Therefore, components that are outside the limits or standard intervals must be repaired or if they cannot be repaired then replaced with new components. Based on the results of existing research, it can be concluded that troubleshooting is a series of systematic activities that include observing symptoms, diagnosing damage, conducting inspections and measurements on systems and components, identifying damage based on the results of inspections and measurements, and determining corrective steps if repairs must be made.